Pengembangan Modul Praktikum Berbantuan PhET Simulation Berbasis Inkuiri Terbimbing Pada Materi Momentum, Impuls dan Tumbukan Kelas X SMA - Raeka Widi Anggeraeni; Indica Yona Okyranida; Luluk Setyowati (UNIVERSITAS INDRAPRASTA PGRI, 2022)
Physics is a subject that has many concepts that must be adapted to the curriculum. Therefore, in the implementation of learning practicum activities are needed as a support so that students can understand a concepts that is difficult to understand. In addition, based on the Circular Letter of the Ministry of Education and Culture Number 4 of 2020, shifting face-to-face learning to the online system. So that the practicum can be carried out virtually using PhET (Physics Education Technology). In conducting virtual practicum, a media that can support learning is needed in the form of a practicum module. And also in learning activities, the material presented by educators is not necessarily all students are able to accept and understand. Thus, the learning model that can be applied is guided inquiry-based learning. This learning media was created whit the aim of facilitating and assisting student in understanding the material presented by educators. This research is a Research & Development (R & D) research with a 4D research model. This learning media is validated and assessed by experts in their fields as well as educational practitioners. The physics practicum module assisted by PhET Simulation based on guided inquiry on momentum, impulse and sollision materials for class X high school obtained an average value od each validation, namely the material expert validation test 87,50% with a very feasible category, the media expert validation test 86,67% with very feasible category, linguistics expert validation test 79,55% with very feasible category, and 94,69% education practitioner test with very feasible category. These result indicate that the physics practicum module assisted by PhET Simulation based on guided inquiry on momentum, impulse and collision material for class X high school that was developed is “very feasible” to be tested on students.